Investigation of the functional properties and subcellular localization of alpha human and rainbow trout estrogen receptors within a unique yeast cellular context. Issue 149 (May 2015) - Le Grand, Adélaïde; Bouter, Anthony; Couturier, Anne; Mulner-Lorillon, Odile; Le Goff, Xavier; Chesnel, Franck; Sire, Olivier; Le Tilly, Véronique
Highlights: Sub-cellular localization of hERα and rtERαS expressed in a same cellular context. Effects of different estrogens on functional properties of hERα and rtERαS . Model assessing for the ligand-independent transcriptional activity of rtERαS . Abstract: Estrogens are steroid hormones that play a pivotal role in growth, differentiation and function of reproductive and non-reproductive tissues, mediated through estrogen receptors (ERs). Estrogens are involved in different genomic and non-genomic cell signaling pathways which involve well-defined subcellular ER localizations. Thus, ER activity results from complex interplays between intrinsic binding properties and specific subcellular localization. Since these two factors are deeply intricate, we carried out, in a unique yeast cell context, a comparative study to better understand structure/function/subcellular distribution relationships. This was carried out by comparing two ERs: the human ER α subtype (hERα) and the short form of the α isoform of the rainbow trout ER (rtERαS ). Their distinct binding properties to agonist and antagonist ligands and subcellular localizations were characterized in Saccharomyces cerevisiae yeast cells. An unexpected partial agonistic effect of ICI 182-780 was observed for rtERαS . Concomitant to distinct binding properties, distinct subcellular localizations were observed before and after ligand stimulation. Due to the unique cell context, the link between ERs intrinsic binding properties and subcellular localizations is partly unveiled and issues are hypothesized based on the role of cytoplasmic transient complexes which play a role in the ER cytoplasmic/nuclear partition, which in turn is critical for the recruitment of co-regulators in the nucleus.